Navigating the future of carbon capture and storage technology: the interplay of social acceptability and political development - Farid Karimi; Ehsan Marzban; Ulrika Dahlberg (Journal of Integrative Environmental Sciences)
Carbon Capture Utilisation and Storage (CC(U)S) technology faces both technical and non-technical challenges that significantly impact its large-scale deployment. This study focuses on socio-political challenges, particularly in the context of recent developments in Europe, such as the Russian invasion of Ukraine. This research is based on an extensive literature review, a stakeholders’ workshop, and an expert survey, leading to a thematic analysis that identifies major socio-political factors influencing CC(U)S deployment in Europe. Our analysis suggests a conceptual framework that addresses these challenges and identifies two core conceptual domains – socio-political context and background environment – as critical factors for the future development of CC(U)S. The findings indicate that political development and social acceptability are pivotal drivers of CC(U)S deployment. Political development is increasingly linking energy security to national security, prompting a shift towards leveraging domestic resources. Social acceptability beyond social acceptance has the potential to become the focus of future discourses. Moreover, the study highlights the importance of trust- a factor that is prevalently discussed in the literature- in policymakers and industry in post-trust societies affected by major events such as the COVID-19 pandemic and the Russian invasion. Finally, we propose a preliminary evaluation model to assess the socio-political readiness of European countries for CC(U)S deployment. The paper concludes by discussing the political implications and recommendations of this study.